The impact of electronic word-of-mouth in social networking sites on a high-involvement purchase : an empirical study of South African brides' intention to purchase the "once-in-a-lifetime" wedding dress - Mowzer, Zeenat (School of Management Studies, 2016)
South Africa is home to a bourgeoning wedding industry valued at $3.25 billion. Much of the profit generated in this industry is from the sales of wedding dresses, with 57.1% of South African brides having purchased a new wedding dress from a bridal boutique in 2013. Previous research has looked at the effect of social media, in the form of electronic word-of-mouth (eWOM), on purchase intention. However, few studies have analysed this effect for high-risk, "once-in-a-lifetime" products such as wedding dresses. In South Africa alone, social media users increased by 20% in 2014, with 29% of the population using social media applications. However, it is uncertain whether this widespread adoption of social media influences the purchase of high-risk, "once-in-alifetime" products like wedding dresses. The "eWOM in SNS's model" is applied to this context, where the influence of eWOM, trust and value co-creation, on the purchase intention of a wedding dress, is compared using an experimental design. One hundred and fifty-two (n=152) engaged South African females, between the age of 18 and 29 years, partook in an experiment. The experiment involved a control group and an experimental group, who viewed eWOM on the Facebook fan page of a wedding dress vendor. The study showed that while the "eWOM in SNS's model" was both valid and reliable in this context, the influence of eWOM on purchase intention was much diminished and fully mediated through value co-creation. The managerial implications of this study's findings, aimed at wedding dress vendors with Facebook fan pages, were all geared towards stimulating value co-creation, given its effect on the relationship between eWOM and purchase intention. The implications involved maximising visual content, appropriately responding to negative comments, publishing posts at suitable times and frequencies, observing the available Facebook reports and posting customer testimonials.